Multiplex profiling of tumor‐associated proteolytic activity in serum of colorectal cancer patients. Issue 5 (12th May 2014) - Yepes, Diego; Costina, Victor; Pilz, Lothar R.; Hofheinz, Ralf; Neumaier, Michael; Findeisen, Peter; Schilling, Oliver; Findeisen, Peter
<x xml:space="preserve">Abstract</x> Purpose The monitoring of tumor‐associated protease activity in blood specimens has recently been proposed as new diagnostic tool in cancer research. In this paper, we describe the screening of a peptide library for identification of reporter peptides (RPs) that are selectively cleaved in serum specimens from colorectal cancer patients and investigate the benefits of RP multiplexing. Experimental design A library of 144 RPs was constructed that contained amino acid sequences of abundant plasma proteins. Proteolytic cleavage of RPs was monitored with MS. Five RPs that were selectively cleaved in serum specimens from tumor patients were selected for further validation in serum specimens of colorectal tumor patients (n = 30) and nonmalignant controls (n = 60). Results RP spiking and subsequent quantification of proteolytic fragments with LC‐MS showed good reproducibility with CVs always below 26%. The linear discriminant analysis and PCA revealed that a combination of RPs for diagnostic classification is superior to single markers. Classification accuracy reached 88% (79/90) when all five markers were combined. Conclusions and clinical relevance Functional protease profiling with RPs might improve the laboratory‐based diagnosis, monitoring and prognosis of malignant disease, and has to be evaluated thoroughly in future studies.